2019
DOI: 10.4252/wjsc.v11.i3.196
|View full text |Cite
|
Sign up to set email alerts
|

Stromal cell-derived factor-1α promotes recruitment and differentiation of nucleus pulposus-derived stem cells

Abstract: BACKGROUND Intervertebral disc (IVD) degeneration is a condition characterized by a reduction in the water and extracellular matrix content of the nucleus pulposus (NP) and is considered as one of the dominating contributing factors to low back pain. Recent evidence suggests that stromal cell-derived factor 1α (SDF-1α) and its receptor C-X-C chemokine receptor type 4 (CXCR4) direct the migration of stem cells associated with injury repair in different musculoskeletal tissues. AIM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…In this study, IVDD resulted in an increased SDF‐1α expression detected by immunohistochemistry in both AF and NP tissues that was decreased after GCSF treatment. These results were in accordance with those of Ying et al (2019), who induced IVDD by needle puncture in rat tails and evaluated SDF‐1α immune expression 4 weeks after surgery. They reported that SDF‐1α immune expression was significantly higher in the IVDD group than the control one.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, IVDD resulted in an increased SDF‐1α expression detected by immunohistochemistry in both AF and NP tissues that was decreased after GCSF treatment. These results were in accordance with those of Ying et al (2019), who induced IVDD by needle puncture in rat tails and evaluated SDF‐1α immune expression 4 weeks after surgery. They reported that SDF‐1α immune expression was significantly higher in the IVDD group than the control one.…”
Section: Discussionsupporting
confidence: 92%
“…For SDF‐1α immune staining, the sections were incubated overnight with SDF‐1α primary antibodies (1:100 dilution) at 4°C. The next day, IVD sections were washed with phosphate‐buffered saline and then incubated for 20 min with horseradish peroxidase‐conjugated goat anti‐rabbit IgG (1:200 dilution) as a secondary antibody at 37°C (Ying et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, promoting cell recruitment of endogenous cell populations for the IVD has been explored as a potential therapeutic strategy [4,5]. Rather than cell transplantation, this strategy proposes the use of chemokines to enhance cell recruitment, avoiding in vitro manipulation.…”
Section: Introductionmentioning
confidence: 99%